Multimodal Analysis of People’s Hectic Life in Apple Advertisement The Whole Working From Home Thing - Andra Setiawan Weltofa; Nani Indrajani Tjitrakusuma (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
This study aims to find out what kind of life is portrayed in the advertisement and how Apple products help people to cope with that life portrayed in the advertisement. This study analyzes Apple advertisement video entitled The Whole Working From Home Thing. This study uses multimodal theory from Paltridge (2012), semiotic mode from Chia & Chan (2017), Mercado (2011), Eiseman (2017), Ekman & Friesen (2003), and Pease (2004). The data analysis uses a qualitative method. The analysis reveals that Apple has successfully created the video that could portray the hectic situation people felt when they could only do their activities inside their home during COVID-19 pandemic. While being busy with their lifestyle, they use Apple products by utilizing its features to help them. Furthermore, this study opens new possibilities for other researchers to apply the same theory that has been used in this thesis to analyze film and video with different topics.